2008
DOI: 10.1371/journal.pone.0001940
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin Functions as a Multivalent Pattern Recognition Receptor with an Opsonic Activity

Abstract: BackgroundVitellogenin (Vg), a major reproductive protein, has been associated with infection-resistant response in fish. However, the underlying mechanisms by which Vg is involved in anti-infectious response are not understood.Methodology/ResultsBy both protein-microbe interaction analysis and enzyme-linked immunosorbent assay as well as phagocytosis test, we demonstrate for the first time that fish Vg acts as a pattern recognition molecule with multiple specificities that can recognize bacteria as well as fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 46 publications
1
105
0
1
Order By: Relevance
“…Knowledge about this protein could, eventually, provide unique illustrations on how insect social organization can be achieved at the level of protein structure. Moreover, insights into the molecular properties of vitellogenins are of broader general interest, as alternative functions of this family of yolk precursor proteins are now surfacing in diverse taxa: including in the immune defense against viruses and bacteria in fish (Garcia et al, 2010;Li et al, 2008;Shi et al, 2006), and in aging in Caenorhabditis elegans (Nakamura et al, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about this protein could, eventually, provide unique illustrations on how insect social organization can be achieved at the level of protein structure. Moreover, insights into the molecular properties of vitellogenins are of broader general interest, as alternative functions of this family of yolk precursor proteins are now surfacing in diverse taxa: including in the immune defense against viruses and bacteria in fish (Garcia et al, 2010;Li et al, 2008;Shi et al, 2006), and in aging in Caenorhabditis elegans (Nakamura et al, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…This lipoprotein has a broad-range of antibacterial, antiviral, and antifungal effects as shown in several fish species [38][39][40][41] . Piscine vitellogenin gene expression is upregulated upon infection -the protein recognizes bacterial and fungal surface components, and facilitates phagocytosis of the pathogens [38] .…”
Section: Vitellogenin In Immunitymentioning
confidence: 99%
“…This lipoprotein has a broad-range of antibacterial, antiviral, and antifungal effects as shown in several fish species [38][39][40][41] . Piscine vitellogenin gene expression is upregulated upon infection -the protein recognizes bacterial and fungal surface components, and facilitates phagocytosis of the pathogens [38] . Using the honey bee as a model, we have shown that insect vitellogenin shares most of the immunological properties identified in fish; honey bee vitellogenin binds to the Gram negative E. coli and the Gram positive honey bee pathogen Paenibacillus larvae, and, more specifically, to the pathogen-associated pattern molecules lipopolysaccharide, peptidoglycan and yeast zymosan [42] .…”
Section: Vitellogenin In Immunitymentioning
confidence: 99%
“…Interestingly, as a major component of yolk proteins, chicken Pv has been shown to be able to inhibit the growth of the Gram-negative bacterium Escherichia coli (29) via chelating ions through its numerous phosphorylated serine residues (30,31). In addition, vitellogenin, the precursor of Pv, has also been revealed to be an antimicrobial agent involved in immune defense in fish (32)(33)(34)(35)(36). Similarly, mosquito vitellogenin has recently been shown to be able to interfere with the anti-Plasmodium response in the malaria mosquito Anopheles gambiae (37).…”
mentioning
confidence: 99%
“…Labeling of rPv with Fluorescein Isothiocyanate (FITC)-Purified rPv (ϳ32 M) and BSA were labeled as described by Li et al (33). The purity of the conjugate, FITC-labeled rPv, was confirmed by SDS-PAGE and Coomassie Blue staining, and its F/P ratio (F/P ratio is defined as the ratio of moles of FITC to moles of protein in the conjugate) was calculated by the equation F/P ϭ (2.77 ϫ A 495 )/(A 280 Ϫ(0.35 ϫ A 495 )) from the absorbance readings of the conjugated samples (42).…”
mentioning
confidence: 99%